2022
DOI: 10.36253/phyto-12965
|View full text |Cite
|
Sign up to set email alerts
|

Genotype variation of citrus tristeza virus after passage on different hosts, and changes in the virus genotype populations by the vector Aphis gossypii

Abstract: Phylogenetic analyses categorize seven genotypes of citrus tristeza virus (CTV). The symptoms caused by this pathogen, their expression and severity are influenced by CTV genotypes, host species, cultivars, and infected host rootstocks. This study aimed to verify how populations of Chilean CTV isolates changed following inoculation from infected sweet orange to Mexican lime trees, and to determine if CTV genotype populations influenced transmission efficiency via Aphis gossypii. Reverse transcription polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our study of the potential variation of the virus in citrus trees revealed that the Sari isolate of CTV had mild variation, which could contribute to the virus’s best fit in different environmental conditions. This potential variation has also been reported in previous studies [ 31 , 32 ], which suggests that it could be a fitness tool for the virus. Our findings add to this body of research and provide new insights into the potential for CTV to adapt to different host environments.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study of the potential variation of the virus in citrus trees revealed that the Sari isolate of CTV had mild variation, which could contribute to the virus’s best fit in different environmental conditions. This potential variation has also been reported in previous studies [ 31 , 32 ], which suggests that it could be a fitness tool for the virus. Our findings add to this body of research and provide new insights into the potential for CTV to adapt to different host environments.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that the CTV genotypes can be changed after passage through different hosts [ 31 ]. Studies demonstrated the existence of genotype population modification in the genotype of a single isolate after passage through two different hosts, demonstrating that the presence and dominance of population genotypes were modified by virus transmission from sweet orange to Mexican lime [ 31 , 32 ]. So, CTV has a variation potential in a population in a host which our results confirm previous studies and these variations can support CTV for best fit in a different situation.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, detecting both pathogens via RT-PCR was only possible after eight months of incubation. In the case of CTV, although CTV isolates naturally correspond to mixed populations of the virus, according to Camps et al [21], they used a VT-type isolate, classified as aggressive because it reacts to the MCA13 antibody [17], and were able to observe vein clearing in the leaves of Arizona citron 861-S1-inoculated plants. In this study, 334 isolates from Mexican lime were obtained initially from a sweet orange in the Pica locality and were classified as VT-type or MCA13-positive [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Pizarro [16], at the Mallarauco locality close, it was determined that the cachexia incidence in this area varied between 10.3 and 36.7%; this area of the country was considered the most affected by this disease [15]. Although the reports by Weathers and collaborators were based on the symptoms observed in the field and with Mexican lima indicator plants, most modern reports have also used serological and/or molecular methods to diagnose the presence of these pathogens, especially CTV and cachexia isolates [12,13,16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation